PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI PILOT PROJECT PEMBANGUNAN DESA PARTISIPATIF DI KABUPATEN MALUKU TENGGARA - DEREK BAKARBESSY (BADATI, 2020)
This study aims to determine and analyze community participation in the Pilot Project for ParticipatoryVillage Development in Southeast Maluku Regency. The results showed that community participation inthe Pilot Project for Participatory Village Development in Southeast Maluku Regency can be said to behigh and mobilized, although there are also some villages that show genuine participation. In relation to thegovernment's position as a stimulator of development, the community will actively participate in adevelopment program in accordance with the level of their needs, so that the program is carried outaccording to the wishes and needs of the community itself. The integrated role between the Governmentand social institutions will increase community participation in participatory development programs.